Indocyanine green angiography for lower incidence of anastomotic leakage after transanal total mesorectal excision: a propensity score-matched cohort study - Chen, Hengkai; Ye, Linfang; Huang, Changyu; Shi, Yingjun; Lin, Fangzhou; Ye, Honghao; Huang, Yongjian (Frontiers in Oncology, 2023)
Background: Anastomotic leakage (AL) is the most serious complication that can arise during colorectal surgery. Indocyanine green (ICG) angiography offers an intraoperative assessment of colonic vascular perfusion in real time. We aimed to assess ICG’s effects on the AL rate in patients who have underwent transanal total mesorectal excision (TaTME) for rectal cancer. Methods: This retrospective cohort study was conducted at our center from October 2018 to March 2022 to analyze the clinical data of patients with rectal cancer who have underwent TaTME after propensity score matching (PSM). The primary outcome was the proximal colonic transaction line modifying and clinical AL rate. Results: One hundred and forty-three patients in non-ICG group and 143 patients in ICG group were included after PSM. Proximal colonic transaction line of 7 patients in non-ICG group was modified while18in ICG group (4.9% vs 12.5%, p=0.023). Twenty-three patients (16.1%) in non-ICG group and 5 patients (3.5%) in ICG group were diagnosed with AL (p<0.001). ICG group had a less hospital readmission rate than non-ICG group (0.7% vs 7.7%, p=0.003). The between-groups differences of basic line and other outcomes were not significant. Conclusions: ICG angiography is a safe and feasible method to help surgeonsto identify the potentially poor colon vascular perfusion and modify the proximal colonic transection line, resulting in a significant reduction in AL and hospital readmission rate.